2014
DOI: 10.2495/cr140201
|View full text |Cite
|
Sign up to set email alerts
|

Modelling a temperature regime of a railway track structure and its comparison with the results of experimental measurements

Abstract: Following the completed experimental monitoring of the temperature regime of the construction of a subgrade structure on the experimental stand of the Departments Railway Engineering and Track Management and measurement of thermal conductivity coefficients λ of building materials used in construction of a subgrade structure, there are constructed mathematical models, which are designed to not only verify the temperatures obtained in individual structural components of subgrade structure of experimental stand, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 1 publication
(1 reference statement)
0
9
0
Order By: Relevance
“…The SoilVision software enables mathematical modelling of various combinations of material compositions of railway track structure after entering all the relevant input data. In this way, conditions for drawing up the relevant design nomograms for various types of subgrade structure or railway body types [1,[4][5][6] are created.…”
Section: Resultsmentioning
confidence: 99%
“…The SoilVision software enables mathematical modelling of various combinations of material compositions of railway track structure after entering all the relevant input data. In this way, conditions for drawing up the relevant design nomograms for various types of subgrade structure or railway body types [1,[4][5][6] are created.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental measurements as well as the numerical modeling of the thermal regime of the rail track (subgrade) confirmed that the air frost index is not the only parameter that influences the depth of rail track freezing (Hodas Ižvolt 2014). In the design methodology of the determination of structural thickness of the protective layer it is also necessary to consider…”
Section: Preliminary Results From the Experimental Monitoring And Nummentioning
confidence: 99%
“…The material of layer used for the numerical model experiment is identical with the material of our "in-situ" models at the Railway Engineering Department, by authors [2] in 2014 and in the world [3], [4] and [5]. The material and technical characteristics of these structural layers R i , which are applied to the MODEL 4, are shown in Tab.1, where: λ -thermal conductivity, ρ -bulk density, c -specific thermal capacity and w -volume content of water.…”
Section: Characteristics Of Layers Of Models and Load From The Externmentioning
confidence: 99%
“…Numerical MODEL 4 represents the winter climatic load in the Poprad area (High Tatras Mountain Range) and the numerical MODEL 5 is increased by 30 % in the freezing effect of MODEL 4. The research was published in 2014 by authors [11], [2] and their climatic loads by the mean daily temperatures T s are shown in Fig. 1.…”
Section: Vol 15 Issue 1 5-12mentioning
confidence: 99%